2012
DOI: 10.3892/ijo.2012.1467
|View full text |Cite
|
Sign up to set email alerts
|

ZGDHu-1 promotes apoptosis of chronic lymphocytic leukemia cells

Abstract: Chronic lymphocytic leukemia (CLL) is a low-grade lymphoid malignancy incurable with conventional modalities of chemotherapy. We aimed to examine the proapoptotic effects of a novel proteasome inhibitor, N,N'-di-(m-methylphenyi)-3,6- dimethyl-1,4-dihydro-1,2,4,5-tetrazine-1,4-dicarboamide (ZGDHu-1), on CLL cells. B lymphocytes were isolated from CLL patients and normal healthy controls, and treated with various concentrations of ZGDHu-1 for different days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…Then the T lymphocytes were removed using anti-CD3 Dynabeads ® (Dynal, Merseyside, UK). The B lymphocytes were further purified by flow cytometric sorting based on CD19 antibody staining (Immunotech, Coulter, uSA) as previously reported (12). B lymphocytes were then counted in a Neubauer Counting Chamber with trypan blue to exclude dead cells.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Then the T lymphocytes were removed using anti-CD3 Dynabeads ® (Dynal, Merseyside, UK). The B lymphocytes were further purified by flow cytometric sorting based on CD19 antibody staining (Immunotech, Coulter, uSA) as previously reported (12). B lymphocytes were then counted in a Neubauer Counting Chamber with trypan blue to exclude dead cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified as a potential proteasome inhibitor (11). It was demonstrated that ZGDHu-1 induces the apoptosis of B lymphocytes from CLL patients (12). In the present study, we investigated ZGDHu-1 used alone or combined with fludarabine in regards to the ex vivo apoptotic effects on CLL cells and normal lymphocytes derived from peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations